AUDIO SCRAPBOOK MEDIA WITH STORYTELLING METHOD TO STIMULATE WORD LEARNING ABILITY IN CHILDREN - Busyro Karim; Shilatur Rihmah (Citra Dharma Cindekia, 2022)
This research aims to develop Scrapbook Audio media to stimulate the ability to ban words in children aged 5-6 years. This research uses the Borg &Gall development model through 4 stages of trials, namely expert trials of materials and languages, expert trials of learning media, initial field trials, and main field trials. The subjects of this study were as many as 9 children, considering that while the study is still in the condition of Covid-19 (Rotating system in the Teacher's house). Data collection techniques use questionnaires and documentation. The results showed that the value obtained by Scrapbook Audio media from material and language experts was 92,5% with the predicate